PREDICTIVE VALUE OF GENERAL BLOOD ANALYSIS INDICATORS TO PREDICT MORTALITY IN ELDERLY PATIENTS - Akhverdiev, B.D.; Kasimov, N.A. (World of Medicine and Biology, 2021)
Management of acute abdominal diseases at senile and elderly patients, prognosis of the outcomes is very important issue of surgery. The purpose of the study was to identify of mortality predictors among the parameters of periphery blood analyses and evaluate the prognostic value in elderly patients. We have analyzed the outcomes of the 216 elderly patients with acute abdomen, who underwent urgent surgical procedure. Results of our study, acquired by binary logistic regression, Pearson correlation and Area Under the Receiver Operating Characteristics analysis revealed that the hemoglobin and white blood count as good predictors. Survival depending of the cut off values for hemoglobin (11.04 g/dl) and white blood count (14.05х103/l) was statistically different. Thus, anemia positively, leukocytosis negatively correlates with outcomes. Hemoglobin values and leukocyte counts have a high predictive value for predicting mortality after emergency surgery in elderly and senile patients.
Keywords: abdominal cavity; hemoglobin; leukocytes; surgical treatment